Italy's native wine grape terroirs - D'Agata, Ian (University of California Press, 2019)
"Italy's Native Wine Grape Terroirs is the definitive reference book on Italy's myriad crus and grand cru wine production areas of Italy's native wine grapes. D'Agata's customary scientific but discursive approach to wine provides an easy to read and enjoyable guide to Italy's best wine terroirs, enriching his descriptions with geologic data, biotype and clonal information, producer anecdotes and interviews, facts and figures compiled over twenty years devoted to wine. The terroirs that give Italy's best wines are described and analyzed in-depth, both well-known (Barolo, Chianti Classico) and not (Grignolino d'Asti, Friuli Colli Orientali Picolit). Everyday wine lovers, beginners and professionals alike, will find this new book to be the perfect complement to D'Agata's previous award-winning Native Wine Grapes of Italy (UC Press)"--Provided by publisher.